2, 6‐Di‐Tert‐Butyl‐Hydroxytoluene and Its Metabolites in Foods. Issue 1 (January 2015) - Nieva‐Echevarría, Bárbara; Manzanos, María J.; Goicoechea, Encarnación; Guillén, María D.
Abstract 2, 6‐Di‐tert‐butyl‐hydroxytoluene (BHT, E‐321) is a synthetic phenolic antioxidant which has been widely used as an additive in the food, cosmetic, and plastic industries for the last 70 y. Although it is considered safe for human health at authorized levels, its ubiquitous presence and the controversial toxicological data reported are of great concern for consumers. In recent years, special attention has been paid to these 14 metabolites or degradation products: BHT‐CH2OH, BHT‐CHO, BHT‐COOH, BHT‐Q, BHT‐QM, DBP, BHT‐OH, BHT‐OOH, TBP, BHQ, BHT‐OH(t), BHT‐OH(t)QM, 2‐BHT, and 2‐BHT‐QM. These derived compounds could pose a human health risk from a food safety point of view, but they have been little studied. In this context, this review deals with the occurrence, origin, and fate of BHT in foodstuffs, its biotransformation into metabolites, their toxicological implications, their antioxidant and prooxidant properties, the analytical determination of metabolites in foods, and human dietary exposure. Moreover, noncontrolled additional sources of exposure to BHT and its metabolites are highlighted. These include their carryover from feed to fish, poultry and eggs, their presence in smoke flavorings, their migration from plastic pipelines and packaging to water and food, and their presence in natural environments, from which they can reach the food chain.